Design and synthesis of new tricyclic indoles as potent modulators of the S1P1 receptor. Issue 3 (1st February 2015) - Buzard, Daniel J.; Schrader, Thomas O.; Zhu, Xiuwen; Lehmann, Juerg; Johnson, Ben; Kasem, Michelle; Kim, Sun Hee; Kawasaki, Andrew; Lopez, Luis; Moody, Jeanne; Han, Sangdon; Gao, Yinghong; et al.
Graphical abstract